Analysis of the treatment regimen efficacy for columnaris disease in Pterophyllum scalare - I. V. Lavrinenko; L. V. Shulga; O. O. Peredera; I. A. Zhernosik (Regulatory Mechanisms in Biosystems, 2020)
The article presents the results of studies on the treatment scheme efficacy for columnaris in Pterophyllum scalare, common under private aquarium husbandry conditions. To establish the diagnosis, the clinical features of the diseased fish, pathological and anatomical changes and the results of microscopic and microbiological studies were taken into account. Separate chemical and microbiological parameters of aquarium water were also studied. It was established that fish disease developed against the background of adverse changes in the chemical composition and microbiocenosis of aquarium water. High alkalinity and excess of phosphates compared to the norm provoked accumulation of opportunistic microbiota, resulting in a balance disorder in the parasite-host system and development of clinical manifestation of the fish disease. During the disease outbreak, bacteriological indices of water indicated a high level of organic contamination and a low intensity of water self-purification processes. Clinically, the disease was manifested in P. scalare by decrease in appetite and motor activity, onset of ulcerative lesions of various shapes and sizes on the surface of the body and on the gill covers. Selected pure cultures of Flavobacterium columnare showed sensitivity to enrofloxacin (growth retardation zone 31.3 ± 1.0 mm); moderate resistance was found to tylosin. The microorganisms were resistant to amoxicillin, doxycycline, benzylpenicillin and tetracycline. Microscopic studies of intestinal specimens of dead P. scalare revealed numerous motile flagellates. It has been shown that an effective treatment regimen that provides recovery for 70% of diseased P. scalare is the use of enroxil 10% solution for five days, metronidazole three times a day, and “API MelaFix” for seven days. It is proved that the following measures are effective to restore the disrupted hydro-balance: periodic water replacement in the amount of 20% of the total volume, providing the aquarium with active aeration systems, planting slow-growing plants and reducing the amount of fish food provided. The measures developed were efficient, they led to elimination of the outbreak of columnaris in the P. scalare and to restoration of biological equilibrium in a closed aquatic ecosystem.